The Conservation of Native Domestic Animal Breeds in Nordic Countries: From Genetic Resources to Cultural Heritage and Good Governance - Ovaska Ulla; Bläuer Auli; Kroløkke Charlotte; Kjetså Maria; Kantanen Juha; Honkatukia Mervi (MDPI, 2022)
Native breeds are domestic animal populations that have adapted to their habitats. The genetic value of breeds has been known for a long time, and recently more attention has been paid to their cultural value. Due to both ecological and cultural significance, it is important that native breeds continue to be bred in their native environments. This is supported by various financial support schemes. Support schemes rarely cover the financial gap in output compared to commercial breeds. A solution to this has been sought in special products, such as cheese or wool, and other businesses, such as animal-assisted care and tourism. Less attention has been paid to the role of administration and good governance in the maintenance of native breeds. In this study, a questionnaire was sent to all registered keepers of native breeds in Finland. This survey clarified their reasons for keeping native breeds and their ideas for improving governance structures and practices. The results were discussed in stakeholder workshops, and in a Nordic context. The results show that genetic and cultural values are recognised in several documents and programmes, but farmers need to be engaged more in the design of support schemes and practices.